DETERMINANTS OF FIRST TRIMESTER SPONTANEOUS ABORTION AMONG PREGNANT WOMEN WHO VISIT YAOUNDÉ HOSPITALS: CASE CONTROL STUDY - Florent, Fouelifack Ymele; Bambo Hetcheu, Pascaline; Ofeh Anyimbi, Mosman; Foumane, Pascal (Ethiopian Journal of Reproductive Health, 2022)
Introduction Abortion is the termination of pregnancy before the period of fetal viability which is 22 weeks according to the WHO. It can be spontaneous or induced. Spontaneous abortion is one of the most common complications of pregnancy and represent 10 to 20% of pregnancy terminations. Our objective was to determine the factors associated with first trimester spontaneous abortion. Methods We conducted a case-control study at the Yaoundé Gyneco-Obstetrics and Pediatric Hospital and the Yaoundé Central Hospital, concerning women received from December 15, 2017 to June 01, 2018. The cases were women whose pregnancy ended in a miscarriage in the first trimester. The controls were pregnant women beyond 14 weeks of pregnancy. Data were analyzed using Epi Info 3.5.4 software. The search for associations between different variables studied was done by the odds ratio with its 95% confidence interval. P was significant for any value <0.05. Results In total we recruited 69 cases for 138 controls. The absence of daily walking, having a spouse employed in the private sector, not having had a prenatal check-up, the occurrence of malaria and history of spontaneous abortion in the 1st trimester were independent risk factors of first trimester spontaneous abortion, with respectively: aOR=4.83; CI=1.3417.38; aP=0.0159, aOR=2.90; CI = 1.51 - 5.58; aP=0.001, aOR=72.02; CI=7.86 - 659.61; aP<0.001, aOR=63.11; CI=4.18 - 952.02; aP=0.003, and aOR=65.01; CI=5.93-711.54; aP=0.001. Conclusion The absence of daily walk, secondary education level, history of abortion, the absence of prenatal check-up and malaria increased the risk of spontaneous abortion in the first trimester. Screening for these factors and intensifying campaigns for Provider Behavior Change Communication would improve the prognosis of pregnancies. Keywords: associated factors, spontaneous abortion, first trimester, pregnancy, Yaoundé